Covert underwater communication by camouflaging sea piling sounds. (15th December 2018) - Liu, Songzuo; Wang, Mengjia; Ma, Tianlong; Qiao, Gang; Bilal, Muhammad
Abstract: To achieve covert underwater acoustic communication, a unique technique of mimicking genuine sea-piling sounds as carrier to convey information is presented. It differs from traditional low signal to noise ratio covert underwater acoustic communication. The communication signal can be detected, but it could not be recognized from the perspective of camouflage to realize covert acoustic communication in the sea. According to the features of sea-piling sounds, a quasi-constant period based pulse position modulation scheme is proposed. First we put each piling sound with identical time interval in time domain and it is moved off the original position with a dedicated time delay which is calculated by modulated information. To make the communication signal akin to the piling sounds, the synchronization header is designed by time hopping pulse position modulation scheme with real piling sounds. At the receiver, basis pursuit algorithm under the theory of compressive sensing is used for channel estimation, and passive phase conjugation technique is used for channel equalization to eliminate the impacts of multipath channel. The feasibility and efficiency of the proposed method are verified by simulation and pool experiment.